Electronic origin of reorganization energy in interfacial electron transfer - Sonal Maroo; Leonardo Coello Escalante; Yizhe Wang; Matthew P. Erodici; Jonathon N. Nessralla; Ayana Tabo; Takashi Taniguchi; Kenji Watanabe; Ke Xu; David T. Limmer; D. Kwabena Bediako (Nature, 2026)
Abstract Electron transfer (ET) reactions underpin energy conversion and chemical transformations in both biological 1,2 and abiological 3–5 systems. The efficiency of any ET process relies on achieving a desired ET rate within an optimal driving force range. Marcus theory 6,7 provides a microscopic framework for understanding the activation free energy—and therefore the rate—of ET in terms of a key parameter: the reorganization energy. For electrified solid–liquid interfaces, it has long been conventionally understood that only factors in the electrolyte phase are responsible for determining the reorganization energy and that the electronic density of states (DOS) of the electrode only serves to dictate the number of thermally accessible channels for ET 5,8–12 . Here we show instead that the electrode DOS plays a central role in governing the reorganization energy, far outweighing its conventionally assumed role. Using atomically layered heterostructures, we tune the DOS of graphene and measure outer-sphere ET kinetics. We find the ensuing variation in ET rate arises from strong modulation in a reorganization energy associated with image potential localization in the electrode. Here we redefine the traditional paradigm of heterogeneous ET kinetics, revealing a deeper role of the electrode electronic structure in interfacial reactivity.